FRI0549 Magnetic Resonance Imaging Structural Alterations Associated with Active Discopathy of the Lumbar Spine: Identification of Two Phenotypically Distinct Subsets of Vertebral Endplate Modic 1 Signal Changes. (9th June 2015) - Nguyen, C.; Jousse, M.; Sanchez, K.; Feydy, A.; Revel, M.; Lefèvre-Colau, M.-M.; Poiraudeau, S.; Rannou, F.
Abstract : Background: Active discopathy detected on magnetic resonance imaging (MRI), and also known as Modic 1 signal changes, encompasses clinical, radiological and biological features, enabling to define a specific subset of patients with chronic low back pain (cLBP). Modic 1 changes are largely associated with degenerative disc disease (DDD) features, however we hypothesized that a specific subset of Modic 1 patients may display milder DDD. Objectives: To determine Modic 1 MRI-associated structural alterations, and to identify Modic 1 subsets based on MRI findings. Methods: MRI computerized database of a tertiary care hospital in France was searched between 01/01/2006 and 01/31/2008. MRI of the lumbar spine were systematically screened by two assessors. When Modic 1 changes were present at a single level on both adjacent endplates, MRI were considered eligible, and demographics and MRI-associated structural changes were assessed. Results: Out of 12, 840 recorded MRI, 101 MRI were eligible. Patients' mean age was 56.6 (13.4) years and 41 (40.6%) were males. Modic 1 changes were more frequent at L4/L5 and L5/S1 levels (37[36.6%], respectively). The most frequent MRI-associated structural alterations were >50% intervertebral space narrowing (IVSN) (70[69.3%]), anterior (51[50.5%]) and posterior (56[55.4%]) disc herniations, and anterior (68[67.3%]) and lateral (59[58.4%]) osteophytes. ≤50% IVSN Modic 1 differed from >50% IVSN Modic 1. On bivariable analysis, patients were younger (51.5[14.1] vs 58.8[12.6] years, p =0.019), ≤50% IVSN Modic 1 were more often located at L5/S1 level (19[61.3%] vs 18[25.7%], p =0.001), and anterior and lateral osteophytes were less frequent (13[41.9%] vs 55[78.6%], p <0.001, and 11[35.5%] vs 48[68.6%], p =0.002, respectively). On multivariable analysis, variables independently associated with >50% IVSN Modic 1 were location at L4/L5 level, anterior disc herniation and lateral osteophyte. Conclusions: Modic 1 changes are frequently associated with MRI DDD features. However, we identified a distinct ≤50% IVSN Modic 1 subset that occurs in younger patients, and is associated with less advanced DDD features. Disclosure of Interest: None declared